2022
DOI: 10.1016/j.medidd.2022.100120
|View full text |Cite
|
Sign up to set email alerts
|

A determination of pan-pathogen antimicrobials?

Abstract: While antimicrobial drug development has historically mitigated infectious diseases that are known, COVID-19 revealed a dearth of ‘in-advance’ therapeutics suitable for infections by pathogens that have not yet emerged. Such drugs must exhibit a property that is antithetical to the classical paradigm of antimicrobial development: the ability to treat infections by any pathogen. Characterisation of such ‘pan-pathogen’ antimicrobials requires consolidation of drug repositioning studies, a new and growing field o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 123 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Although some IAs display magic bullet PPP, I maintain that all derive their PPP from their network pharmacological, immunomodulating properties ( Fig. 3 ) [ [261] , [262] ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…Although some IAs display magic bullet PPP, I maintain that all derive their PPP from their network pharmacological, immunomodulating properties ( Fig. 3 ) [ [261] , [262] ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…The probiotic isolates showed moderate antibacterial activity against Staphylococcus aureus. The diameter of the inhibition zone was categorized into low, moderate, and high antimicrobial activity, based on the size of the inhibition zone (Prathapan, 2022). The table of antimicrobial test results indicated that S1-3 had the lowest inhibition zone size of 1.90 inches/mm, indicating low antimicrobial activity, while S3-3 had the highest inhibition zone size of 7.17 inches/mm, indicating high antimicrobial activity (Figure 1).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Importantly, we also highly urge all researchers to separate the trials using nitazoxanide for mild–moderate COVID-19 from those using it to manage severe COVID-19 (Rocco et al 2022 ) in all future meta-analysis studies and to focus mainly on its early use to manage COVID-19. Interestingly, some excellent reviews have thoroughly discussed the potential and available clinical evidence when nitazoxanide is repurposed to manage COVID-19 (Al-kuraishy et al 2022 ; Firth and Prathapan 2021 ; Kelleni 2022b ; Lokhande and Devarajan 2021 ; Mahmoud et al 2020 ; Prathapan 2022 ).…”
mentioning
confidence: 99%